2013
DOI: 10.1590/s1519-99402013000400001
|View full text |Cite
|
Sign up to set email alerts
|

Características morfológicas e produtivas da maniçoba cultivada sob lâminas hídricas e doses de nitrogênio

Abstract: Rev. Bras. Saúde Prod. Anim., Salvador, v.14, n.4, p.609-623 out./dez., 2013 http://www.rbspa.ufba.br ISSN 1519 9940 609Características morfológicas e produtivas da maniçoba cultivada sob lâminas hídricas e doses de nitrogênio RESUMOObjetivou-se com este ensaio avaliar o comportamento da maniçoba cultivada sob irrigação e doses de nitrogênio. O delineamento experimental utilizado foi o de blocos completos casualizados em arranjo fatorial (7 x 4), sendo sete lâminas totais de água (394,28, 333,16, 279,20, 213… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
1
0
0
1
Order By: Relevance
“…For the variables carrying capacity (CCAP), WAC and WUE, it was observed that the increase of the nitrogen levels (0, 100, 200 and 400 kg N ha -1 ) provided increasing linear increments, being observed that the higher the level of nitrogen the higher the cactus pear production (Table 2). However, the same pattern was not observed on NUE, which presented decreasing linear effect, and this behavior was similar to those found by Araújo Filho et al (2013), who obtained maximum N efficiency at the lowest nitrogen level (50 kg ha -1 ), associating this effect to the higher assimilation and lower nutrient loss by leaching or volatilization to the environment. In the present study, the lowest level tested (100 kg N ha -1 ) presented the best efficiency, which means it took a lower amount of N applied to produce one kg of accumulated DFMY, and this efficiency reduced as the N level applied increased.…”
Section: Resultssupporting
confidence: 88%
“…For the variables carrying capacity (CCAP), WAC and WUE, it was observed that the increase of the nitrogen levels (0, 100, 200 and 400 kg N ha -1 ) provided increasing linear increments, being observed that the higher the level of nitrogen the higher the cactus pear production (Table 2). However, the same pattern was not observed on NUE, which presented decreasing linear effect, and this behavior was similar to those found by Araújo Filho et al (2013), who obtained maximum N efficiency at the lowest nitrogen level (50 kg ha -1 ), associating this effect to the higher assimilation and lower nutrient loss by leaching or volatilization to the environment. In the present study, the lowest level tested (100 kg N ha -1 ) presented the best efficiency, which means it took a lower amount of N applied to produce one kg of accumulated DFMY, and this efficiency reduced as the N level applied increased.…”
Section: Resultssupporting
confidence: 88%
“…Apesar do déficit hídrico ser mais drástico em estádios reprodutivos, o acúmulo de massa de matéria seca da parte aérea não parece ter sido drasticamente afetado nesse período, pois a planta está direcionando o seu metabolismo para o desenvolvimento das sementes que estão sendo formadas; nessa etapa há pouco crescimento e expansão foliar, além disso, caso a planta não tenha capacidade de fornecer o suprimento adequado para a expansão foliar, ela irá utilizar de suas reservas, retranslocado-as das folhas mais velhas para os pontos de crescimento (ARAÚJO-FILHO et al, 2013).…”
Section: Desenvolvimento Das Plantasunclassified